2011
DOI: 10.1186/1756-0500-4-147
|View full text |Cite
|
Sign up to set email alerts
|

Etiological spectrum and treatment outcome of Obstructive jaundice at a University teaching Hospital in northwestern Tanzania: A diagnostic and therapeutic challenges

Abstract: BackgroundObstructive jaundice poses diagnostic and therapeutic challenges to general surgeons practicing in resource-limited countries. This study was undertaken to highlight the etiological spectrum, treatment outcome of obstructive jaundice in our setting and to identify prognostic factors for morbidity and mortality.MethodsThis was a descriptive prospective study which was conducted at Bugando Medical Centre between July 2006 and June 2010. All patients with a clinical diagnosis of obstructive jaundice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
47
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 16 publications
25
47
3
4
Order By: Relevance
“…Similar observation has been reported in a recent study by Chalya et al (2011). The duration of illness has been reported to be an important predictor of outcome in patients with obstructive jaundice (Han et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Similar observation has been reported in a recent study by Chalya et al (2011). The duration of illness has been reported to be an important predictor of outcome in patients with obstructive jaundice (Han et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…In this review, patients with malignant obstructive jaundice were found to be older than those of benign type. Similar age distribution was also reported previously by Chalya et al (2011) at the same centre.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations